1995
DOI: 10.1172/jci117945
|View full text |Cite
|
Sign up to set email alerts
|

Receptors for atrial natriuretic peptide are decreased in the kidney of rats with streptozotocin-induced diabetes mellitus.

Abstract: To determine whether decreased renal responsiveness to atrial natriuretic peptide (ANP) in diabetes is mediated by alterations in the renal ANP receptor, ANP receptor density and affinity were measured 17-20 d after streptozotocin injection and compared with values in vehicle-treated controls and streptozotocin-treated rats made euglycemic with insulin. Plasma ANP concentration was significantly greater in hyperglycemic diabetic rats than in control or euglycemic diabetic rats. Both in glomeruli and inner medu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 49 publications
4
22
0
Order By: Relevance
“…In streptozotocin-induced diabetes, these acute effects of BNP were preserved, unlike those of bradykinin or ACE or neutral endopeptidase inhibition. The cyclic GMP-response to BNP was blunted in diabetic hearts, suggesting a potential downregulation of cardiac NP A receptors, as has been reported in the diabetic kidney (25). However, the BNP-induced rise in cyclic GMP was clearly sufficient to counter the response to angiotensin II.…”
Section: Discussionsupporting
confidence: 57%
“…In streptozotocin-induced diabetes, these acute effects of BNP were preserved, unlike those of bradykinin or ACE or neutral endopeptidase inhibition. The cyclic GMP-response to BNP was blunted in diabetic hearts, suggesting a potential downregulation of cardiac NP A receptors, as has been reported in the diabetic kidney (25). However, the BNP-induced rise in cyclic GMP was clearly sufficient to counter the response to angiotensin II.…”
Section: Discussionsupporting
confidence: 57%
“…This may be important physiologically because studies have shown that increased osmolarity resulting from uncontrolled diabetes is an important factor in causing the vascular complications associated with this disease. In fact, NPR-A is desensitized in animal models (19) as well as in human subjects (20) with uncontrolled insulin-dependent diabetes. It is therefore quite possible that a mechanism similar to the one we described for NPR-B may explain this process.…”
Section: Discussionmentioning
confidence: 99%
“…Because the role of this fundamental mechanism in the regulation of NPR-A and NPR-B remains ambiguous and because receptor down-regulation has been implicated in the desensitization of natriuretic peptide receptors that accompanies various pathologies, such as congestive heart failure (Tsutamoto et al, 1993;Kim et al, 1999) and diabetes (Sechi et al, 1995), we initiated experiments designed to resolve these important issues. For the first time, we measured both the desensitization and internalization of NPR-A and NPR-B in the same cell system.…”
mentioning
confidence: 99%